Effect of spiral scan strategy on microstructure for additively manufactured stainless steel 17–4. (August 2021) - Yeung, H.; Chen, J.; Yang, G.; Guo, Y.; Lin, D.; Tan, W.; Weaver, J.
Abstract: The effect of the scan strategy on microstructure is investigated using a custom-built laser powder bed fusion additive manufacturing testbed. Eight stainless steel cubic parts were built to compare two different scan strategies: raster and spiral. The processes were monitored in-situ by a high-speed camera coaxially aligned to the heating laser, and the parts built were characterized by micro-indentation and optical microscopy. The spiral scan strategy creates a much larger meltpool area and the resulting parts exhibit an equiaxed grain structure with 54% higher hardness value compared to the raster scan strategy.